1996
DOI: 10.1207/s15327752jpa6601_4
|View full text |Cite
|
Sign up to set email alerts
|

Rorschach Measures of Posttraumatic Stress in Persian Gulf War Veterans: A Three-Year Follow-Up Study

Abstract: The long-term psychological effects of war-related stress were assessed with the Rorschach 3 years after the Persian Gulf War. Rorschach data are presented for 30 U.S. Marine reservists at a 3-year follow-up who reported experiencing symptoms of posttraumatic stress (PTS) initially after Operation Desert Storm (ODS), and for 25 Marine reservist controls who did not participate in ODS. Results showed significant differences over time between the initial evaluation data and follow-up, and between initial evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 8 publications
1
15
0
1
Order By: Relevance
“…We have found that PTSD subjects access combatrelated imagery (CC) more readily than their counterparts, replicating the results of Sloan et al [1996]. However, it is notable that few subjects appear to be overly distracted by these images.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…We have found that PTSD subjects access combatrelated imagery (CC) more readily than their counterparts, replicating the results of Sloan et al [1996]. However, it is notable that few subjects appear to be overly distracted by these images.…”
Section: Discussionsupporting
confidence: 74%
“…To index traumatic preoccupation, we used two variables proposed in previous Rorschach studies of PTSD. Following Sloan et al [1995Sloan et al [ , 1996, we assigned Combat Content (CC) to responses that included one of the following criteria: 1) articles of war/weapons; 2) military apparel; 3) an object that has been shot, stabbed, or blown up; 4) personalized experience of combat operations; and 5) animals, vegetation, geographical features associated with the Vietnam War theater of operations. Additionally we used Burch's [1993] combat-related content index [(Bl + An + Hd + Fi + Ex)/R], a summary score calculated for each subject, derived from existing Exner variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypervigilance is identified by a positive Hypervigilance Index (HVI), which suggests a cautious, mistrustful approach to people and events, preferably at a distance rather than up close. Further information about these and other Rorschach variables commonly associated with traumatic stress disorder is provided by Armstrong and Kaser-Boyd (2004), Holaday (2000), Luxenberg and Levin (2004), Sloan, Arsenault, and Hilsenroth (2002), and Sloan, Arsenault, Hilsenroth, Handler, and Harvill (1996).…”
Section: Irving B Weiner 105mentioning
confidence: 99%
“…These findings demonstrate how coping is undetermined by the acute and chronic management of intrusive thoughts and sense of helplessness that constitute substantial factors in traumatic experience (Wilson & Keane, 1997). Furthermore, Sloan, Arsenault, Hilsenroth, Handler, and Harvill (1996) found that the signifycantly lowered D and AdjD scores of those exposed to war stressors disappeared in a follow-up study conducted three years after the initial collection of data.…”
Section: Introductionmentioning
confidence: 98%